Reporting the level of evidence in the Canadian Journal of Plastic Surgery: Why is it important? - Thoma, Achilleas (Pulsus Group Inc, 2012)
The levels of evidence (LOE) table has been increasingly used by many surgical journals and societies to emphasize the importance of proper study design. Since their origin, LOE have evolved to consider multiple study designs and also the rigour of not only the study type but multiple aspects of its design. The use of LOE aids readers in appraising the literature while encouraging clinical researchers to produce high-quality evidence. The current article discusses the benefits and limitations of the LOE, as well as the LOE of articles published in the Canadian Journal of Plastic Surgery (CJPS). Along with an assessment of the LOE in the CJPS, the authors have provided recommendations to improve the quality and readability of articles published in the CJPS.